PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY (AR) PADA MATA PELAJARAN SBDP MATERI TARI TRADISIONAL KELAS V SDN 015 LOA KULU KABUPATEN KUTAI KARTANEGARA - Muhlis; Safitri, Astri; Ramli Buhari, Muh.; Mustamiroh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of instructional media which is limited to the SBdP subject of traditional dance makes students at SDN 015 Loa Kulu feel less interested and experience learning difficulties. As many as 100% of students have never used media-based learning augmented reality. Therefore, it is necessary to develop media-based learning augmented reality. This study aims to determine the product in the form of media-based learning augmented reality in SBdP learning traditional dance material for class V SDN 015 Loa Kulu has met the valid, practical, and effective criteria.The research method used is Research and Development (R&D) with the ADDIE development model. The research instrument is in the form of product validation, item questions posttest and response questionnaires which were validated by media experts, material experts and grade V teachers. The selection of respondents was carried out using the method purposive sampling and involved 10 students of class V as the research sample. Data analysis was performed using Aiken's V and descriptive statistics.The results showed that the product met the very valid criteria with a validation percentage of material experts of 97.5%, media experts of 100%, and class V teacher validation of 100%. The results of the student response questionnaire have fulfilled the very practical criteria with an average percentage of 98.88% and an average percentage value posttest 93% which met the very effective criteria. Thus, learning media based augmented reality can be used in the learning process, because it meets valid, practical and effective criteria.